Antioxidant Activity and Phytochemical Screening of Rhizopora mucronata Mangrove Leaf Extract from Mangrove Botanical Garden, Surabaya City, Esat Java - Rahmawati, Rahmawati; Sanjaya, Yushinta Aristina; Pratiwi, Yunita Satya; Hendrawan, Elistiya Putri Nuraini; Salsabila, Zhafa Nesya; Amalia, Tania (Universitas Gadjah Mada, 2025)
Rhizophora mucronata is a type of mangrove plant that acts as a natural antioxidant which is used as a food ingredient and traditional medicine. The aim of this research was to determine the profile of secondary metabolites, antioxidant activity and total phenols of R. mucronata leaf extract. R. mucronata leaves were obtained from Gunung Anyar District, Surabaya City and then extracted using three solvents with different polarities, namely n-hexane, ethyl acetate, and ethanol. Mangrove leaf extract (Rhizopora mucronata) was followed by phytochemical testing using color testing, antioxidant activity testing using the DPPH method, and determining phenol content using the Folin-Ciocalteu method. Phytochemical tests show that all R. mucronata mangrove leaf extracts contain secondary metabolites such as flavonoids, saponins, steroids, triterpenoids and tannins with total phenols ranging from 0.04%-6.7%. The antioxidant activity of n-hexane, ethyl acetate, and ethanol extracts were 4.9 mg ± 0.82%, 1.7 mg ± 0.17%, and 0.21 mg ± 1.9%, respectively.